Reporting detection of Chlamydia trachomatis DNA in tissues of neonatal death cases - Maria Hernandez Trejo; Norma E. Herrera Gonzalez; Marcos R. Escobedo Guerra; M. de Jesus de Haro Cruz; Elsa R. Moreno-Verduzco; Marcela Lopez-Hurtado; Fernando M. Guerra-Infante (Elsevier, 2014)
OBJECTIVE: to determine whether C. trachomatis was present in neonates with infection, but without an isolated pathogen, who died during the first week of life. METHODS: early neonatal death cases whose causes of death had been previously adjudicated by the institutional mortality committee were randomly selected. End-point and real-time polymerase chain reaction of the C. trachomatis omp1 gene was used to blindly identify the presence of chlamydial DNA in the paraffinized samples of five organs (from authorized autopsies) of each of the dead neonates. Additionally, differential diagnoses were conducted by amplifying a fragment of the 16S rRNA of Mycoplasma spp. RESULTS: in five cases (35.7%), C. trachomatis DNA was found in one or more organs. Severe neonatal infection was present in three cases; one of them corresponded to genotype D of C. trachomatis. Interestingly, another case fulfilled the same criteria but had a positive polymerase chain reaction for Mycoplasma hominis, a pathogen known to produce sepsis in newborns. CONCLUSION: the use of molecular biology techniques in these cases of early infant mortality demonstrated that C. trachomatis could play a role in the development of severe infection and in early neonatal death, similarly to that observed with Mycoplasma hominis. Further study is required to determine the pathogenesis of this perinatal infection.